2009
DOI: 10.1021/ja902558j
|View full text |Cite
|
Sign up to set email alerts
|

Hydrazides as Tunable Reagents for Alkene Hydroamination and Aminocarbonylation

Abstract: The author has granted a nonexclusive license allowing Library and Archives Canada to reproduce, publish, archive, preserve, conserve, communicate to the public by telecommunication or on the Internet, loan, distribute and sell theses worldwide, for commercial or noncommercial purposes, in microform, paper, electronic and/or any other formats. L'auteur a accorde une licence non exclusive permettant a la Bibliotheque et Archives Canada de reproduire, publier, archiver, sauvegarder, conserver, transmettre au pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
1
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(39 citation statements)
references
References 27 publications
0
37
1
1
Order By: Relevance
“…The thioimidate moiety could also be hydrolyzed efficiently to the cyclic hydrazide 17 . Such pyrazolidinones can undergo N – N -bond cleavage to prepare β-homoproline amide derivatives, 15 for use in β-peptides. 16 A novel desulfurizative reduction of 3a in the presence of AgOTf also provided direct entry to the corresponding pyrazolidine 18 .…”
Section: Resultsmentioning
confidence: 99%
“…The thioimidate moiety could also be hydrolyzed efficiently to the cyclic hydrazide 17 . Such pyrazolidinones can undergo N – N -bond cleavage to prepare β-homoproline amide derivatives, 15 for use in β-peptides. 16 A novel desulfurizative reduction of 3a in the presence of AgOTf also provided direct entry to the corresponding pyrazolidine 18 .…”
Section: Resultsmentioning
confidence: 99%
“…

A method based on hydroamination mediated by inorganic base was developed for the synthesis of cyclic nitrones from alkenyl oximes. [2][3][4][5][6] Retro-Cope hydroamination of alkenyl oximes has also been studied. The transition state of this reaction is stabilized by an ionic interaction between a metal cation such as K + and the oxime oxygen and negatively charged alkene moiety.

Hydroamination of unsaturated carbon-carbon bonds (alkenes or alkynes) is one of the most efficient methods to construct nitrogen-containing heterocyclic scaffolds in an atom-and step-economical manner.

…”
mentioning
confidence: 99%
“…Recently, we reported that amphoteric amino‐ and imino‐isocyanates can be formed in situ under mild conditions and engage in high‐yielding alkene cycloadditions6ac and nucleophilic additions,6d,e despite their known tendency to dimerize or oligomerize 7. 8 Hydrazones6bd and hydrazides6a,e are bench‐stable, convenient “blocked” N ‐substituted isocyanate precursors9 that form the desired isocyanates via an equilibrium induced under mild conditions, and then react with nucleophiles such as amines, alcohols, and thiols 6de. Using this reactivity, we developed a cascade substitution/hydroamination sequence allowing rapid assembly of saturated nitrogen heterocycles from hydrazide starting materials 6e.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, N , N ‐dibenzylcarbazate 1 c (Table 1, entry 7) also cyclized in good yield. In contrast to the previous examples (LG=OPh; Table 1, entries 1–6), a temperature of 150 °C was required to ensure the formation of the amino‐isocyanate intermediate using O t Bu as a leaving group 6a. This leaving group was chosen to facilitate the synthesis of the starting material ( 1 c ), due to the lability observed during the formation of OPh derivative.…”
Section: Methodsmentioning
confidence: 99%